Melanin‐based coloration covaries with fluctuating asymmetry, nutritional state and physiological stress response in common snipe. (11th November 2013) - Minias, Piotr; Kaczmarek, Krzysztof; Włodarczyk, Radosław; Janiszewski, Tomasz
<x xml:space="preserve">Abstract</x> Adaptative significance of melanin‐based coloration in birds remains poorly recognized. It has been suggested that genes responsible for melanin synthesis may have pleiotropic effect on several physiological and behavioural functions, including immune defence. For this reason, we could expect that the expression of melanin‐based plumage coloration should covary with different condition‐related phenotypic traits via regulation of pathogen/parasite resistance. The aim of this study was to test this hypothesis in common snipe Gallinago gallinago, a species that exhibits conspicuous variation in the black eumelanism of underwing plumage. The study was conducted in central Poland, where common snipe were captured during autumn migration. We found that after accounting for the effects of age, sex and date of capture, underwing coloration correlated with nutritional state of snipes, as more extensively melanised individuals had higher plasma concentrations of triglycerides, total protein and albumin. Dark underwing coloration was also associated with lower heterophil/lymphocyte (H/L) ratio, suggesting better resistance of eumelanic individuals to physiological stress. Finally, adult males with darker underwings had lower asymmetry in wing shape (wingtip convexity), which indicated their higher developmental stability. In conclusion, melanin‐based coloration may be considered an honest indicator of phenotypic quality in common snipe.